Efficacy and safety of weekly versus triweekly cisplatin treatment concomitant with radiotherapy for locally advanced nasopharyngeal carcinoma: A systematic review and pooled analysis - Tian, Xin; Zhu, Qiuxia; Zhang, Zhenyong (Frontiers in Pharmacology, 2023)
Background:Most nasopharyngeal carcinoma cases are diagnosed at an advanced stage due to their hidden anatomical structure and atypical clinical symptoms and often require chemoradiotherapy. Here, we present a systematic review and pooled analysis to synthesize existing research results of the efﬁcacy and adverse effects of weekly versus triweekly cisplatin chemotherapy concomitant with radiotherapy for locoregionally advanced nasopharyngeal carcinoma (LANPC). Methods:We searched PubMed, Embase, and the Cochrane Library from inception to September 1, 2021, for relevant original research articles published in English. The literature search and data extraction were done independently by two investigators. We used random-effects models to provide point estimates (95% conﬁdence interval [CI]) of overall response rate (ORR), overall survival (OS), progression-free survival (PFS), locoregional recurrence-free survival (LRFS), distant metastasis-free survival (DMFS) and the incidence rate of adverse effects (AEs) and with subgroup analysis according to each study type. The primary endpoints were ORR, OS, and PFS; LRFS, DMFS, and grade ≥3 acute AEs were secondary endpoints. Results: In total, 2,305 patients of 8 studies were included in this review. We found that patients administered cisplatin weekly or triweekly had no differences in ORR, OS, PFS, DMFS, LRFS, severe mucositis, dermatitis, nausea/vomiting nor nephrotoxicity. Patients administered weekly cisplatin were at a higher risk of hematological toxicity compared to that in patients who received the chemotherapy triweekly. Conclusion:Our findings suggest that both regimens could be recommended as the standard of care for the chemoradiotherapy treatment of LANPC, the perceived benefit of lower toxicity with weekly cisplatin could not be established.